PELATIHAN TEKNIK DASAR PENGELASAN (WELDING) BAGI SISWA DI DESA BAHAGIA - Bagus Imam Prasetyo; Yopi Handoyo; Sugeng Sugeng (An-Nizam, 2022)
The “Welding Basic Technique Training For Students In Bahagia Village” focuses on transferring technology and expertise to form entrepreneurship that has been applied to the community and has high economic value. Equipping the community with materials and knowledge about welding technology is expected to be a motivation for the younger generation in particular and the community as well as opening up business opportunities to create jobs that will later become useful activities.